Emerging IO checkpoints in gastrointestinal oncology - Tojjari, Alireza; Saeed, Anwaar; Cavalcante, Ludimila (Frontiers in Immunology, 2025)
Recent progress in immunotherapy has significantly altered the therapeutic approach for gastrointestinal cancers, which are historically challenging due to their intricate pathologies and unfavorable outcomes. This review emphasizes the growing importance of immune checkpoints like TIGIT, VISTA, GITR, STING, and TIM-3 in the treatment of gastrointestinal oncology. These checkpoints are crucial elements within the tumor microenvironment, presenting new therapeutic possibilities. Studies show that TIGIT and GITR regulate the functions of T cells and NK cells, while the VISTA and STING pathways boost the body’s anti-tumor responses. TIM-3 is linked with T cell fatigue, highlighting its potential as a target to counteract immune evasion mechanisms. Integrating these immune checkpoints with traditional treatments could result in more customized and effective therapeutic approaches. This detailed review seeks to explore the changing field of immune checkpoint research, offering insights from molecular biology to clinical practice, and envisioning a future where advanced treatment methods greatly enhance patient outcomes in GI cancers.